Matrix‐assisted laser desorption/ionization imaging protocol for in situ characterization of tryptic peptide identity and distribution in formalin‐fixed tissue. (18th February 2013) - Gustafsson, Ove J. R.; Eddes, James S.; Meding, Stephan; McColl, Shaun R.; Oehler, Martin K.; Hoffmann, Peter
Abstract : RATIONALE: Matrix‐assisted laser desorption/ionization (MALDI) imaging mass spectrometry provides the means to map the in situ distribution of tryptic peptides in formalin‐fixed clinical tissue samples. The ability to analyze clinical samples is of great importance to further developments in the imaging field. However, there is a requirement in this field of research for additional methods describing the characterization of tryptic peptides by MALDI imaging. METHODS AND RESULTS: This protocol gives highly detailed instructions, with examples, for (1) successfully performing tryptic peptide MALDI imaging on formalin‐fixed cancer tissue using a MALDI‐TOF/TOF MS instrument, (2) tentatively generating identifications through nLC/MS/MS, and (3) validating these identifications by in situ MS/MS of peptides of interest. CONCLUSIONS: This protocol provides a detailed and straightforward description of the methods required for groups new to MALDI imaging to begin analysis of formalin‐fixed clinical samples. Copyright © 2013 John Wiley & Sons, Ltd.